Engineering the system of communication for safer surgery - Healey, A; Nagpal, K; Moorthy, K; Vincent, C (2011)
Communication failures are a leading cause of error in surgery. Researchers and practitioners have therefore developed different interventions to improve communications, such as team briefing and pre-operative patient checklists. These different methods have clear merit. However, they have only dealt with portions of a complex system. Consequently, disparate interventions of varying kinds may not integrate and build an effective system of communication. We argue that a new view of communication is needed to improve safety in surgery; the view that communication is more fundamentally as a property of the whole system of work rather than confined to interpersonal exchanges. Rather than simply add an intervention to the system, interventions should integrate into the system. To achieve this, we propose a practical strategy to re-engineer the system of communication for surgery. This demands an analysis of the immediate informational needs within the system of interest, and an account of the wider system and those ergonomic and human factors shaping the performance of communicators. We illustrate the application of the method and refer to potential improvements in safety. © 2010 Springer-Verlag London Limited.